Pemanfaatan Sekam Padi sebagai Katalis Zeolit ZSM-5 Mesopori melalui Metode Sintesa Double dan Bebas Template untuk Konversi Metanol - Fusia Mirda Yanti; Sumbogo Murti SD; Yuni K. Krisnandi; Adiarso . (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Rice husk is an abundantly available agricultural waste material containing maximum amount of siliceousash. Burning of rice husk in air produces rice husk ash containing 85-98 % silica. In this research, rice huskash and coal fly ash were used as raw materials for catalyst of ZSM-5 zeolite synthesis. Coal Fly ash wasadded to adjust the source of alumina. ZSM-5 zeolite was synthesized through hydrothermal treatment usingdouble templates (TPAOH and PDDA) and free template. The as-synthesized ZSM-5 was then characterizedusing FTIR, XRD, SEM-EDX, and BET. From the result of characterization, ZSM-5 has been success to besynthesized from rice husk ash. After ZSM-5 was synthesized, the catalytic activities of ZSM-5 were tested toconvert methane to methanol. The result showed that catalytic activity of ZSM-5 double template onmethanol convertion was 7.08 % and free template was 10.54 %. It means, rice husk ash was potential to beused as catalyst for the conversion of methane to methanol.